2009
DOI: 10.1002/maco.200805164
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion characteristics of Al‐Si‐Mg/SiCp composites with varying Si/Mg molar ratio in neutral chloride solutions

Abstract: The corrosion resistance of Al-Mg-Si/SiC p composites produced by the pressureless infiltration method [using SiC p preforms with 50% porosity containing rice hull ash (RHA) and four custom-made alloys with varying Si/Mg molar ratio] was evaluated in neutral 0.1 M NaCl solutions. The deleterious phase Al 4 C 3 was successfully suppressed in composites with Si/Mg molar ratios of 0.89 and 1.05, but not in those with lower Si/Mg molar ratios (0.12 and 0.49). Results of cyclic polarizations in deareated 0.1 M NaCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Also, the electrolyte temperature was kept at 25°C since most industrial applications of Al-Mg 2 Si composite occur at ambient temperature. Further, most previous studies on the corrosion behaviour of Al-Mg 2 Si composite used this temperature and solution; thus this investigation could be comparable to them [9,10]. Then, the weight loss was measured according to the ASTM G31 standard.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, the electrolyte temperature was kept at 25°C since most industrial applications of Al-Mg 2 Si composite occur at ambient temperature. Further, most previous studies on the corrosion behaviour of Al-Mg 2 Si composite used this temperature and solution; thus this investigation could be comparable to them [9,10]. Then, the weight loss was measured according to the ASTM G31 standard.…”
Section: Methodsmentioning
confidence: 96%
“…Although corrosion behaviour is another critical property of the Al–Mg 2 Si composites, in addition to mechanical properties, previous studies have not adequately addressed it. Escalera-Lozano et al [9] investigated the electrochemical and coupling behaviours of Al–Mg–Si alloys containing Mg 2 Si and Si particles. They reported that Si and Mg 2 Si particles acted as cathode and anode, respectively, in the first stages of the corrosion period, which resulted in the selective dissolution of Mg in Mg 2 Si particles.…”
Section: Introductionmentioning
confidence: 99%
“…al., 1997). In another recent investigation, the author´s group focused on the role of Al 4 C 3 in the corrosion characteristics of Al-Si-Mg/SiCp composites with varying Si/Mg molar ratio in neutral chloride solutions (Escalera-Lozano et. al, 2009).…”
Section: Corrosion Behaviormentioning
confidence: 99%
“…This combination of high specific properties makes AMCs interesting for structural elements in the transport industry . Moreover, ceramic particles commonly employed as reinforcement such as silicon carbide (SiC) or titanium diboride (TiB 2 ) present high strength, stiffness, and excellent fatigue and wear resistance . These mechanical properties can also be improved by a decrease of reinforcement size, from micrometric to nanometric size .…”
Section: Introductionmentioning
confidence: 99%